(untitled) (American Journal of Islam and Society, 2003)
Modern Muslim thinkers who try to locate and construct constitutional tenets based on the Islamic tradition face various difficulties, for they have to address a segment of an audience that expects an exposition comparable to the West’s in terms of terminologies, institutions, and remedies, as well as to draw from the best practices of Islamic history and modern Muslim societies. It is always fustrating to learn that Islam’s constitutional history, despite its richness in individual constitutional tenets, loses some of its utility in modern Muslim societies due to systemic changes caused by glob alization and pervasive international institutions, both of which have had far-reaching consequences on domestic sociopolitical settings. Given the contemporary nation-state’s overarching authority, one known guarantee of the people’s social, legal, or political rights is a con stitutional framework under a credible rule of law system. Mohammad Hashim Kamali’s Freedom, Equality and Justice in Islam identifies the three themes in the title of his book as the fundamental bases upon which all other constitutional guarantees of human rights depend. The book is divided into three chapters, each dedicated to one of the main themes. The first chapter, which discusses freedom, presents a conceptual analysis of the term and how it is expressed in Islam’s theological and sociopolitical contexts. However, unlike various guarantees provided for realizing other values, such as justice (discussed in chapter 3), there is little discussion of such practical guarantees for personal liberty and freedom. The author acknowledges that Muslims have given scant attention to constitutional guarantees of freedom, citing the prevalence of despotic governments throughout much of Islamic history. Nevertheless, the only way he offers out of this situation is to observe that Muslims should change the language of fiqh (Islamic jurisprudence) to reflect the challenging times confronting the ummah. This may not be surprising, given the identified problems, as mentioned above, that have to be faced squarely. The second chapter, which analyzes equality, reviews authoritative Islamic sources and argues that although there is conclusive evidence that Islam envisages equality in basic rights and duties among all Muslims, the evidence is somewhat inconclusive on whether all members of the human race enjoy such equality. This inconclusiveness is due to sources that leave room for different interpretations and to prevailing circumstances during the formative period of Islamic law. Kamali pays particular attention to the duties and rights of women and non-Muslims, for there are different opinions on women’s political and family-law rights and on equal opportunity for non-Muslims. He states that even if differential treatments of the two categories are maintained in certain circumstances, such differences do not negate equality, because Islam’s positive equality ...